(3GdJUQja def YLR Yf GdJCdjas - (3Nda Hf YHGS GdRgQGhqj GdCfOdSj, CHh GdbGSe,J (B427 (3g` s
(3ChdgG (B:s
(3jHOC GdehLhO efg HUaI cjajg GSJNQGL GdCajhf s
(3BNQgG (B:s
(3jfJgi HGdaUd GdNGeS hGdKdGKjf ai CfhGY Gdachc GdJi Jchf eY LQGMI s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B310 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B105s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
Keywords: (3GdWHs